Brightness discrimination and contrast sensitivity in chronic glaucoma--a clinical study. Issue 4 (April 1990) - Teoh, S L; Allan, D; Dutton, G N; Foulds, W S
Abstract : The visual acuity, the difference in sensitivity of the two eyes to light (brightness ratio), and contrast sensitivity were assessed in 28 patients with chronic open angle glaucoma and compared with those of 41 normal controls of similar ages and visual acuity. The results obtained were related to the results of Tübingen visual field analysis in patients with glaucoma. Twenty-four of the 28 glaucoma patients (86%) had a significant disparity in brightness ratio between the two eyes. This was found to match the frequency of visual field loss. Moreover, there was a significant relationship between the interocular differences in brightness sense and the difference in the degree of visual field loss between the two eyes. Of the glaucoma patients 39% had sum contrast sensitivities outside the normal range for age-matched normal controls. No significant correlation was found between the interocular difference in brightness sense and the visual acuity or the interocular difference in sum contrast sensitivity. It is concluded that, in the presence of a normal visual acuity, the brightness ratio test warrants evaluation as a potential screening test for chronic open angle glaucoma.